Strategy of Development Religious Culture in Forming Student Character - Khoirun Nisa'; Egydia Savitri N D (SCHOOLAR: Social and Literature Study in Education, 2023)
At this time the moral damage that hit people's lives also penetrated the lives of students, so that students were influenced by a culture that damaged all aspects, especially morals. The occurrence of morality that engulfs this society has an impact on juvenile delinquency. This study aims to describe the strategy of developing religious culture in shaping the character of the MA AL IHSAN Kalikejambon Tembelang students. This research use desciptive qualitative approach. This study is intended to describe the strategies for developing religious culture by making programs to support the application of religious culture so that it can form good character for students. Data collection techniques using interviews, observation, and documentation. The collected data were interpreted and analyzed by reducing data, presenting data, and drawing conclusions. The results of the study reveal that the strategies in the formation of religious culture are: (1) program formation, (2) implementation, (3) application, (4) habituation. While programs in developing religious culture in shaping the character of MA AL IHSAN students through: (1) extracurricular activities (khitobah, recitation, Islamic band and banjari), (2) daily activities (implementation of 3S, dhuha prayer in congregation and dhuhur prayer together ' ah), (3) activities in the month of Ramadan (study of the yellow book and distribution of zakat fitrah by students), (4) PPM (Community Service). The impact and benefits obtained are the formation of better student character and madrasas will become superior and character madrasah.